2006
DOI: 10.3200/genp.133.3.257-276
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Validity of Scores From an Instrument Designed to Measure Metacognition of Problem Solving

Abstract: The authors' purpose in this study was to gather evidence on the validity of scores on an instrument designed to evaluate levels of metacognition in problem solving--Swanson's 15-item metacognition questionnaire (1990, 1993). Forty-three participants took part in this study: 21 professors and 22 graduate students from several Western and Midwestern campuses in the fields of psychology and educational psychology. A Kendall Coefficient of concordance (W) was performed to determine the consistency of ranked respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Past research has found that well‐ and ill‐structured problems require different sets of skills and processes, and therefore performance should be evaluated independently, taking into account the different problems’ objectives (Jonassen, ; Shin, Jonassen, & McGee, ; Sigler & Tallent‐Runnels, ). The objective for Task 1 was defined as “score as many points as you can,” while for Task 2 it was “keep your tribe safe.” Performance in Task 1 was measured with each participant's total cumulative score.…”
Section: Methodsmentioning
confidence: 99%
“…Past research has found that well‐ and ill‐structured problems require different sets of skills and processes, and therefore performance should be evaluated independently, taking into account the different problems’ objectives (Jonassen, ; Shin, Jonassen, & McGee, ; Sigler & Tallent‐Runnels, ). The objective for Task 1 was defined as “score as many points as you can,” while for Task 2 it was “keep your tribe safe.” Performance in Task 1 was measured with each participant's total cumulative score.…”
Section: Methodsmentioning
confidence: 99%
“…Metacognition is an active process of knowing, or being acutely aware of one's cognitive state with the ability to complete a given task. Psychologists and educators recognize the need to guide students to solve complex problems and have proceeded to enhance students' abilities in this area …”
Section: Introductionmentioning
confidence: 99%
“…Psychologists and educators recognize the need to guide students to solve complex problems and have proceeded to enhance students' abilities in this area. 10 Ireland, Johnson, Adams, Eboh and Mowatt conducted an opinion survey of participants in a blended learning course in nursing and midwifery education. 11 The module was rated by all 36 participants as useful, although their opinions on the online discussion part of the module were mixed.…”
Section: Introductionmentioning
confidence: 99%
“…2007). Psychologists and educators recognize the need to teach students to solve complex problems and have proceeded to enhance students’ abilities in this area (Sigler & Tallent‐Runnels 2006). They further advocate that methods be developed to facilitate the solving of ill‐structured problems.…”
Section: Introductionmentioning
confidence: 99%
“…Students without adequate metacognitive skills would have difficulty following a teacher's instructions to identify relevant information or understand cause and effect relationships (Garrett et al 2007). Psychologists and educators recognize the need to teach students to solve complex problems and have proceeded to enhance students' abilities in this area (Sigler & Tallent-Runnels 2006). They further advocate that methods be developed to facilitate the solving of ill-structured problems.…”
Section: Introductionmentioning
confidence: 99%